Short-term outcome of ceramic-on-ceramic total hip replacement in young adult patients (Medical Journal of Indonesia, 2015)
Background: Ceramic-on-ceramic (CoC) total hip replacement (THR) was developed to minimize debris and osteolytic reaction. The major concern is its brittleness. The aim of this study was to evaluate the short-term outcome of CoC THR in young adult patients. Methods: 11 patients, 13 THR procedures, were followed up until six months after surgery in Cipto Mangunkusumo Hospital. Evaluation included Harris hip score (HHS), visual analog scale (VAS), patients' complaint, short form-36 (SF-36), and acetabular and femoral component angles. Data were analyzed using Wilcoxon signed rank test, paired t-test, and Spearman test. Results: The average age of the patients was 33.6 years old and 55% of them were female. Systemic lupus erythematosus was the main causative disease for THR. The VAS average decreased before surgery and after six months of surgery (5 to 1). Pre- and post-operative HHS and SF-36 increased significantly by (25 to 92) and (21 to 54) respectively. Squeaking sound was reported by two patients. No correlation was found between acetabular and femoral component and squeaking incidence. Conclusion: CoC THR showed excellent short term outcome for young adult patients. With proper indications, CoC THR ensures excellent clinical outcomes and promising survivorship.